PENGARUH AKTIVITAS BELAJAR TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN SOSIOLOGI KELAS XI IPS MAN 2 PONTIANAK - Yuliantika, Vista; Bahari, Yohanes; Alhidayah, Riama (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the effect of learning activities on student learning outcomes in learning sociology class XI IPS at MAN 2 Pontianak. The method used is descriptive quantitative research. The data source of this study was students of class XI IPS and the data were in the form of answer sheets for student questionnaires and midterm test scores. The results of research on learning activities are based on respondents' questionnaire answers, namely by percentage of visual activities (48%), oral activities (51%), listening activities (48%), writing activities (38%), drawing activities (40%), motor activities ( 38%), mental activities (34%), emotional activities (38%). The learning results obtained are known from 88 students, there are 61 students who are in the high category, which means reaching the value of KKM for sociology subjects, 27 students in the medium category and no students in the low category. The effect of learning activities on learning outcomes based on the value of t count 2,302> t value table 1,987 then Ho is rejected and Ha is accepted. It can be concluded that there is a significant effect between learning activities on the learning outcomes of XI IPS class students at Man 2 Pontianak. With the percentage contribution of learning activities to learning outcomes by 0.06% while the rest is influenced by other variables not examined in this study. Keywords: Influence, Learning Activities, Learning Outcomes